How Far Upstream: A Review of Estuary-Fresh Water Fish Movements in a Large Neotropical Basin - Fontoura, Nelson Ferreira; Schulz, Uwe Horst; Alves, Thaís Paz; Silveira, Thiago Cesar Lima; Pereira, Joana Jordão; Antonetti, Débora Alessandra (Frontiers in Marine Science, 2019)
The present study comprises the first systematic analysis of the limits of upstream movement by some fish species that use the estuarine area of the Patos Lagoon basin in southern Brazil. The Sinos River sampling program included 86 sites, sampled from 1998 to 2014, covering lowland stretches and headwater streams. The Guaíba sampling program was conducted from February 2011 to March 2013 and comprised 59 independent samples. Six fish species using estuarine areas occur in the upper Patos basin, 250–500 km from the Patos Lagoon outlet to the Atlantic Ocean. Parapimelodus nigribarbis specimens ranged from 11.3 to 18.9 cm (median = 13.3 cm) in length, i.e., were adults (Sinos, n = 459; Guaíba, n = 149). The species was captured almost 500 km from the Patos outlet, as far as 180 km upstream in the Sinos main channel. In Guaíba Lake, the species was captured mainly in autumn, although it was more abundant in winter and spring in the Sinos River. Lycengraulis grossidens was captured in the Sinos Basin, restricted to the lower stretches in spring and summer months (n = 7). In Guaíba Lake (n = 134) the species occurred throughout the lake and year-round, and was ten times more abundant in spring. Most specimens were adult (8.2–26.9 cm, median = 20.0 cm). Most Micropogonias furnieri individuals (n = 63) were juveniles (10.7–33.4 cm, median = 14.2 cm). The species was not captured in the Sinos Basin. In Guaíba Lake M. furnieri occurred predominantly in the southernmost part (downstream) and was more abundant (>10×) in winter. Genidens genidens (n = 27) was captured only in summer in the southern part of Guaíba Lake (closest to the outlet). Most individuals were adults (24.5–34.0 cm, median = 27.8 cm). Genidens barbus (n = 7) was restricted to spring and summer months and was captured only in southern (near-outlet) parts of Guaíba Lake, comprising mainly large juveniles and adults (31.5–68.0 cm, median = 37.9). Mugil liza (n = 13) appeared in spring in relatively low abundances but was widespread throughout Guaíba Lake during the summer. The species was not captured in the Sinos sampling program. The size profile comprised specimens nearing maturity (34.3–45.5 cm, median = 38.9 cm). Finally, we suggest possible biological cycles for these species that combine these new distribution data with published information.